Cambios en la posición de mercado de las empresas Colombianas (2011)
This work seeks to establish the factors that impact on the changes of state between types of companies, following the Boston Consulting Group’s Growth- Share Matrix. Estimations have been performed using a Multinomial Logit Model using data from Superintendencia de Sociedades de Colombia. Results indicate that financial variables affect in similar ways all categories of companies, while industrial organization variables have different effects that depend on the categories. The outcomes suggest that there is a wide spectrum that can be used to formulate economic policies.